Fading channel estimation for free-space continuous-variable secure quantum communication. (17th December 2019) - Ruppert, László; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C; Elser, Dominique; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph
Abstract: We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.